Biomechanics of jumps in rhythmic sport gymnastics (RSG). Kinematic analysis of the principal jumps in RSG - Sousa, F.; Lebre, E. (1998)
INTRODUCTION: The aim of this study was to analyze the fundamental kinematic parameters and the technique used in RSG to perform the `leap jump`, the `leap jump with trunk extension and foot at head`, the `corso jump with trunk extension and foot at head`, and the `lateral removal jump`. These jumps are the basic jumps in RSG and the most usual in the routines of high level RSG gymnasts. METHODS: Twenty-nine junior high level RSG gymnasts aged 12.9±1.1years, 36.4±6.4 Kg weight and 152.8±8.2 cm height, and seventeen senior high level RSG gymnasts aged 15.7±1.1 years, 47.6±5.5 Kg weight and 165.0±6.2 cm height were observed. Each gymnast performed the four different jumps of their routines, and an international judge selected the best of three attempts. The jumps were filmed and analyzed using the Peak 5 System (Peak Performance Technologies Inc. - Video and Analog Motion Measurement Systems), and the different kinematics parameters observed were: duration of the take off, flight phase and total time of the jumps; horizontal distance traveled; height of the center of mass (CM) at take off, highest point, and the total height of the jumps; linear velocity of CM at take off (horizontal, vertical and resultant); angle of outlet at take off; angle of maximal removal of lower legs during the flight phase; trunk/thigh angle at the highest point of the jump and finally the minimal trunk/thigh angle reached during the flight phase. RESULTS AND CONCLUSIONS: The main results of the kinematics parameters show that in both groups of gymnasts the kinematic structure of the basic jumps in RSG may be described solely according to the following parameters: duration of the take off, duration of the flight phase, height of the CM on take off, height of the CM at the highest point, linear velocity of CM at take off (horizontal and vertical), angle of outlet on take off and angle of maximal removal of lower legs during the flight phase. The angle of outlet at take off was the kinematic parameter with the greatest influence on the performance of the junior and senior high gymnasts during the execution of these jumps. REFERENCES: Lisitkaja, T.S. (1985). Ginnastica Ritmica. Societa` Stampa Sportiva, Rome, Italy. Manoni, L. (1986). Analisi Biomeccanica Computerizzata con Metodo Cinematografico della Doppia Enjambèe. Gymnica, Primo Semestre. Micheles, C.; Ruat, M. (1997). Classification des Sauts à partir de l`étude des Actions Motrices Déclenchées pendant la Phase Aérienne. GRS: Le Sens d`une Évolution. Insep-Publications 18-19,123-129.